Cerebrospinal-fluid profile in neuroborreliosis and its diagnostic significance - Bednárova, J (Folia microbiologica, 2006)
Selected cerebrospinal-fluid (CSF) parameters (intrathecal synthesis of Borrelia-specific antibodies, oligoclonal IgG bands, CSF-to-serum quotient of albumin as a marker of blood-CSF barrier function and cytology) and typical CSF profile in neuroborreliosis were evaluated with the aim of elucidating possible clinical and laboratory similarities of neuroborreliosis (NB) and other neurological diseases (OND). From the cohort of 58 patients (38 diagnosed for NB, 20 with OND) NB patients had positive Borrelia-specific IgG antibodies in 97 % and positive Borrelia-specific IgM antibodies in 55 %; oligoclonal IgG bands were detected in 55%. The blood-CSF barrier was impaired in 89%, positive cytology was detected in 97% of the NB patients. Evaluation of specific intrathecal synthesis improves CSF diagnosis of NB, therefore, a combined CSF analysis has to be considered along with the clinical picture and medical history when formulating the diagnosis of NB.
Keywords: sérový albumin; Humans; diferenciální diagnóza; Borrelia burgdorferi Group; imunoglobulin G; hematoencefalická bariéra; Nervous System Diseases; Blood-Brain Barrier; protilátky bakteriální; lymská neuroborelióza; Diagnosis, Differential; lidé; Serum Albumin; Antibodies, Bacterial; Histocytochemistry; mozkomíšní mok; Borrelia burgdorferi komplex; nemoci nervového systému; Cerebrospinal Fluid; imunoglobulin M; Lyme Neuroborreliosis; histocytochemie; Immunoglobulin G; Immunoglobulin M